Metabolic Syndrome Prevalence among Armed Forces Personnel (Military Personnel and Police Officers): A Systematic Review and Meta-Analysis. Issue 9 (27th June 2019) - Rostami, Hosein; Tavakoli, Hamid Reza; Rahimi, Mohammad Hossein; Mohammadi, Mohammad
Abstract: Introduction: Metabolic syndrome (MetS) is closely linked to type 2 diabetes and cardiovascular disease. Various studies have reported the prevalence of MetS in different armed forces personnel in different countries. However, performing a systematic review and meta-analysis on this subject seems necessary. The aim of this study was to estimate the pooled prevalence of MetS among armed forces personnel including members of the military and police forces. Materials and Methods: A systematic review was carried out on all associated papers published in PubMed, Scopus, Web of Science and Cochrane Library, encompassing the timeframe: November, 2018 to January 2000. The overall prevalence of MetS, and its prevalence based on different diagnostic criteria [National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP III), American Heart Association (AHA) and International Diabetes Federation (IDF)] were pooled using a random-effects model. Results: Twenty five eligible studies were selected for the meta-analysis. Among all police officers contained in this study group, the overall prevalence of MetS was 26.2% (95% CI: 19.7–34%; Q = 229.45, p = 0.00). Among different military personnel contained in this study group, the overall estimation of MetS prevalence was 8.3% (95% CI: 6.3–11%; Q = 540.88, p = 0.00) the prevalence of MetS was 8.0% (95% CI: 5.7–11%; Q = 409.76, p = 0.00) according to the NCEP-ATP III criterion. Conclusion: The findings from the present meta-analyses displayed a low prevalence of metabolic syndrome in armed forces in general. These findings will allow healthcare providers and policy-makers to find solutions in order to take action to reduce MetS risks on a wider scale, especially among police officers.